Chromosomal Studies of some Mangrove Species - Sidhu, S. S. (Indian Forester, 1962)
The paper deals with the importance and need of the cytological studies of man- groves. The chromosome number of 9 species of mangroves have been reported for the first time. Intra as well as interspecific polyploidy has been found in the genus Suaeda. The polyploid races and species are more hardy and widely distributed. 18 is the basic number of the family Rhizophoraceae. The separation of Sonneratiaceae from Lytbraceae is indicated by cytological evidences. Most of the mangrove species possess higher chromosome numbers as compared to the corresponding numbers in other species of the same genus or genera of the same family growing under mesic conditions.